2015
DOI: 10.1088/0029-5515/55/12/125001
|View full text |Cite
|
Sign up to set email alerts
|

Neoclassical plasma viscosity and transport processes in non-axisymmetric tori

Abstract: Neoclassical transport processes are important to the understanding of plasma confinement physics in doubly periodic magnetized toroidal plasmas, especially, after the impact of the momentum confinement on the particle and energy confinement is recognized. Real doubly periodic tori in general are non-axisymmetric, with symmetric tori as a special case. An eight-moment approach to transport theory with plasma density N, plasma pressure p, mass flow velocity V and heat flow q as independent variables is adopted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 352 publications
(837 reference statements)
5
95
0
Order By: Relevance
“…4. One can notice that U 1θ,i ≈ 0 in the axisymmetric limit, as is expected from conventional neoclassical literature 23,25 , but is enhanced by an order of magnitude for the helical core in the core region. Additionally, this geometrical enhancement only appears in the flux through a factor of M 2 * /(1 + M 2 * ).…”
Section: B Simulations For a Helical Core Equilibriumsupporting
confidence: 76%
See 1 more Smart Citation
“…4. One can notice that U 1θ,i ≈ 0 in the axisymmetric limit, as is expected from conventional neoclassical literature 23,25 , but is enhanced by an order of magnitude for the helical core in the core region. Additionally, this geometrical enhancement only appears in the flux through a factor of M 2 * /(1 + M 2 * ).…”
Section: B Simulations For a Helical Core Equilibriumsupporting
confidence: 76%
“…To complete the solution of the parallel flow, a prescription for the parallel flow velocity in 3D magnetic fields can be obtained through the Shaing-Callen neoclassical model 23 in the appropriate regimes. We assume that both the impurities and background ions are in the high-collisionality Pfirsch-Schlüter regime.…”
Section: A Collisions and Inclusion Of Neoclassical Effectsmentioning
confidence: 99%
“…It was reported that the existence of i/2p = 1/2 near the edge of the e-ITB can realize higher central electron temperature [14]. And it is pointed out that the strong shear of the radial electric field at the boundary of the magnetic island in the helical plasma can contribute to the reduction of transport through turbulence suppression by E × B shear [24]. This mechanism can explain that higher t e_reff ≤ 0.25m is obtained with the existence of i/2p = 1/2 near the edge of the e-ITB compared to the case when i/2p = 1/2 is vanished by co ECCD superimposed on the counter NBI, as described above.…”
Section: Co Eccd Superimposed On the Balanced Nbimentioning
confidence: 99%
“…Neoclassical toroidal viscosity (NTV) is a physical effect caused by the non-ambipolar diffusion of ions and electrons. 36 The effect can be created by the application of nonaxisymmetric fields in a tokamak, and has been demonstrated to provide an actuator for plasma rotation in NSTX. 37 Depending on the spectrum of the non-axisymmetric field applied, NTV can be created over significant portions of the plasmas.…”
Section: Neoclassical Toroidal Viscosity (Ntv)mentioning
confidence: 99%
“…Results could strongly influence the design of future fusion reactors like the fusion nuclear science facility FNSF, [3][4][5] by helping to understand some key physics issues such as non-inductively sustaining a plasma at high normalized beta, b n . [6][7][8][9][10][11] The two main components of the upgrade are the complete replacement of the NSTX-U center stack by 36 22-footlong, 350-pound copper conductors which contain the inner-leg of the toroidal field (TF) coils, the ohmic heating (OH) solenoid, and some divertor coils, and the addition of a second neutral beam injector, oriented more tangentially compared to the old set for NSTX. This will enable the temperature inside NSTX-U to exceed the 15 Â 10 6 C core of the sun, it will double the toroidal field (TF) capability reaching about 1.0 T, and will also double the plasma current reaching about 2.0 MA.…”
Section: Introductionmentioning
confidence: 99%